The Long and Winding Road to Convert an Antimicrobial Compound into an Antimicrobial Drug: An Overview from a Medicinal Chemistry Point of View - D. Enriz, Ricardo; D. Suvire, Fernando; A. Andujar, Sebastian; A. Alvarez, Maria; Vettorazzi, Marcela; G. Dolab, Juan; Rojas, Sebastian (Current Organic Chemistry, 2017)
Background & Objective: Fungi are responsible for producing infections in humans. While all humans are susceptible to these disorders, immunocompromised people are the most at risk. Although it appears that we have many antifungal drugs in clinical use, unfortunately, most antifungal drugs currently in use have serious limitations or some drawbacks in pharmacokinetic aspects such as they do not possess an adequate solubility. As complement, fungi have developed a significant resistance against them because of their indiscriminate and even irrational use in some cases. Considering such situation, there is an urgent need to develop new and more effective antifungal drugs. Discussion: For such reason, in recent years there has been an incredible increase in the number of studies looking for new compounds with antifungal effects; in particular new structures obtained from natural products. While a large number of compounds with antifungal activities (some of them with novel structures) have been reported, very few have managed to be used therapeutically. In this review article, we have identified and discussed the main reasons for the poor results that have been obtained so far in order to find new antifungal drugs. Also, new strategies which could be under way to improve the search for new antifungal agents for therapeutic use are discussed here, remarking their scope and limitations.
Keywords: target-based screening